CMAC for speech emotion profiling - Kamaruddin, Norhaslinda; Abdul Rahman, Abdul Wahab (2009)
Cultural differences have been one of the many factors that can cause failures in speech emotion analysis. If this cultural parameter could be regarded as noise artifacts in detecting emotion in speech, we could then extract pure emotion speech signal from the raw emotional speech. In this paper we use the amplitude spectral subtraction (ASS) method to profile the emotion from raw emotional speech based on the affection space model. In addition, the robustness of the cerebellar model arithmetic computer (CMAC) is used to ensure that all other noise artifacts can be suppressed. Result from the speech emotion profiling shows potential of such technique to visualize hidden features for detecting intra-cultural and inter-cultural variation that is missing from current approach of speech emotion recognition